VALIDITY OF THE PROBLEM BASED INTRUCTION (PBI) ORIENTED MODULE FOR CLASS VIII STUDENTS IN LIGHT MATERIALS AND OPTICAL (Universitas PGRI Sumatera Barat, 2022)
This research is motivated by the lack of interest in learning physics and the unavailability of interesting learning materials that are suitable for student characteristics and can support the creation of innovative learning. This study aims to produce a new product in the form of a valid PBI-oriented physics learning module. This type of research is development research using a 4D mosel (four-D Model),the research procedure used is 4-D, namely definition, design, development, dissemination due to time and cost limitations. then this step is not implemented. The research instrument used was the initial analysis sheet, the validity sheet. From the results of the research conducted,it was found that the problem based instruction-oriented learning module was categorized as very valid with an average overall score of 82.24%. This research resulted in a problem based instruction (PBI) oriented physics learning module on light materials and optical instruments for class VIII which was very valid.